Kesiapsiagaan Karangtaruna Mengurangi Bencana Banjir di Kelurahan Pasarkliwon Kecamatan Pasarkliwon Surakarta - Irani, Agus Budi; , Drs. Suharjo, M.S (2017)
Natural disasters continue to pose a major threat in many countries including Indonesia one of the threats of disasters in Indonesia are floods. So in need of knowledge, attitude and good mobilization to face the floods, as was done in the village school Pasarkliwon Surakarta. The research was done at Village Pasarkliwon Surakarta entitled "Reducing Flood Disaster Preparedness Karangtaruna in the Village Pasarkliwon Surakarta". The study aims to (1) Getting the results as well as evidence of public awareness of disaster preparedness flooding in the Village district Pasarkliwon Surakarta after using audio-visual media, (2) Determine the public response in addressing flood mitigation in the Village Pasarkliwon. The method used in this research is quantitative descriptive. The data collection technique using the technique of questionnaires, interviews, observation, documentation, field notes, and the prerequisite test. Data analysis technique used is the technique of descriptive statistics using SPSS version 15.0. The results obtained in this study were (1) the level of knowledge Karangtaruna against flood preparedness in the Village Pasarkliwon Surakarta after using audio-visual media, (2) Improvement of community preparedness in dealing with flood mitigation in the Village Pasarkliwon Surakarta. Keywords: Knowledge, Attitude, and Floods Natural